ナンキョク ショウワ キチ ニオケル ランリュウ カンソク 1 - 安達, 隆史; アダチ, タカシ; ADACHI, Takashi (国立極地研究所, 1973)
P(論文) Wind velocity and temperature fluctuations were observed at Syowa Station by means of an ultra sonic anemometer thermometer during JARE 12 (1971-72). In this paper the power spectra and the probability density distribution are mainly studied. The behaviour of the power spectra in changing stability is consistent with the precedent observations. The power spectra pattern of vertical wind component is not always similar to the temperature spectra. Especially in the high frequency range the decrease of power density with frequency in vertical wind spectra is steeper than that in temperature spectra. Moreover, some peaks are seen at the frequency higher than the Brunt-Vaisala frequency. The cause of this phenomenon has not been ascertained yet. The probability density distributions of the wind and temperature fluctuations are similar to the Gaussian distribution, and the joint distributions of them also may be approximated by the Gaussian distribution. The presumed semi-normal joint probability distribution, which is used for the closed system of the correlation tensor equations, has been verified. departmental bulletin paper